Orthogonal partial least squares model for rapid prediction of antioxidant activity of Pereskia bleo by fourier transform infrared spectroscopy - Sharif, K. M.; Rahman, Md. Mokhlesur; Azmir, Jannatul; Khatib, Alfi; Shamsudin, Siti Hadijah; Mohamed, A.; Ferdosh, Sahena; Sarker, Md. Zaidul Islam (Taylor & Francis Inc., 2014)
Pereskia bleo is a species of primitive cactus. In the present study, infrared spectroscopy was used to characterize the antioxidant activity of P. bleo leaves by multivariate analysis. A total of twenty-four extracts were prepared in different solvents. Antioxidant activities were measured by 1,1-diphenyl-2-picrylhydrazyl assay and fingerprinted by infrared spectroscopy between 4000 and 400 cm−1 at a resolution of 2 cm−1. A three component multivariate orthogonal partial least squares model with R2Y of 0.88 and Q2 of 0.86 was developed to correlate infrared spectra with antioxidant activity and evaluated by internal cross-validation and a true external test. For external validation, bioactivity of new extracts of P. bleo was predicted using the model, and -OH, -NH, and -CH were identified as functional groups responsible for the activity. In summary, a successful orthogonal partial least squares model was developed using infrared spectroscopy as a rapid method to predict antioxidant activity.